Bird species occupancy trends in Southeast Mexico over 1900–2020: Accounting for sighting record absences. Issue 3 (23rd December 2022) - Levey, Dallas R.; Patten, Michael A.; Estrada, Alejandro
Abstract: Long‐term land‐use change impacts tropical bird communities through population‐level and functional diversity effects from habitat loss, degradation and fragmentation, leading to land management and conservation challenges. Assessing the temporal impacts of land‐use change on occupancy patterns, population change and functional traits of bird species in tropical areas is limited by the treatment of nondetections as true absences or artefacts of low sampling effort during and throughout years. With this in mind, we developed a novel Bayesian species occupancy framework to account for species absences to evaluate bird community changes in Palenque, Chiapas, Mexico, where there is opportunity for study given exceptional records of change across habitats from rainforest to urban centres. We created a novel dataset of population trends for 244 bird species over the years 1900 to 2020 from published short‐term field studies, expert field notes and community science pages. Our results show that open area species had higher population increases than forest specialists over time, represented most evidently by the turnover of rainforest specialists for urban species. Modelled influence of functional traits displayed the importance of main habitat types, body mass and habitat and dietary breadth as factors that associated with bird population trends. On average, species with body masses <6.6 and > 948.4 g showed decreasing trends, while all other species showed increasing or stable trends. Our findings illuminate the value of accounting for species absences from several data sources to discover long‐term species population trends and affiliated functional traits whose preservation requires conservation and land management action to protect bird ecosystem services. Primary forest conservation is key to maintaining populations of habitat and dietary specialists, such as small understorey insectivorous and large frugivorous species. Protecting rare natural savanna patches from conversion to cattle pasture is vital to prevent further extirpation of native granivores and to slow colonization by exotic and invasive species. Abstract : This article accounts for species absences before occupancy analyses, addressing a long‐standing concern of whether absence is true or due to low sampling effort. The authors affiliate long‐term bird species trends with functional traits in a lowland tropical rainforest landscape in southeast Mexico to help guide land management and conservation efforts. RESUMEN: El cambio a largo plazo en el uso de la tierra impacta a las comunidades de aves tropicales a través de los efectos de la diversidad funcional y a nivel de la población debido a la pérdida, degradación y fragmentación del hábitat, lo que lleva a desafíos de gestión y conservación de la tierra. La evaluación de los impactos temporales del cambio de uso de la tierra en los patrones de ocupación, el cambio de población y los rasgos funcionales de las especies de aves en áreas tropicales enfrenta limitaciones al considerar el tratamiento de las no detecciones como ausencias verdaderas o artefactos de bajo esfuerzo de muestreo durante el año y los años. La evaluación de los impactos temporales del cambio de uso de la tierra en los patrones de ocupación, el cambio de población y las características funcionales de las especies de aves en áreas tropicales está limitada por el tratamiento de las no detecciones como verdaderas ausencias o artefactos de bajo esfuerzo de muestreo durante y a lo largo de los años. Con esto en mente, desarrollamos un marco bayesiano novedoso de ocupación de especies para dar cuenta de las ausencias de especies para evaluar los cambios en la comunidad de aves en Palenque, Chiapas, México, donde existe la oportunidad de estudiar dados los registros excepcionales de cambios en los hábitats, desde la selva tropical hasta los centros urbanos. Creamos un nuevo conjunto de datos de tendencias de población para 244 especies de aves durante los años 1900 a 2020 a partir de estudios de campo a corto plazo publicados, notas de campo de expertos y páginas de ciencia comunitaria. Nuestros resultados muestran que las especies de áreas abiertas tuvieron aumentos de población más altos que los especialistas forestales a lo largo del tiempo, representado más evidentemente por la rotación de especialistas de bosques tropicales por especies urbanas. La influencia modelada de los rasgos funcionales mostró la importancia de los principales tipos de hábitat, la masa corporal y el hábitat y la amplitud de la dieta como factores asociados con las tendencias de la población de aves. En promedio, las especies con masas corporales <6, 6 g y >948, 4 g mostraron tendencias decrecientes, mientras que todas las demás especies mostraron tendencias crecientes o estables. Nuestros hallazgos iluminan el valor de contabilizar las ausencias de especies de varias fuentes de datos para descubrir tendencias de población de especies a largo plazo y rasgos funcionales afiliados cuya preservación requiere acción de conservación y manejo de la tierra para proteger los servicios ecosistémicos de las aves. La conservación de los bosques primarios es clave para mantener las poblaciones de especialistas en hábitat y dieta, como las especies insectívoras pequeñas del sotobosque y las especies frugívoras grandes. Proteger los raros parches naturales de sabana de la conversión en pastos para ganado es vital para evitar una mayor extirpación de los granívoros nativos y para retrasar la colonización por especies invasoras.